CuZnAl spinel solid solution catalyst as well as preparation method and application thereof

By introducing Zn components into the copper-aluminum spinel catalyst, adjusting the sustained release rate of copper and the migration of Al, the problem of catalyst instability caused by the fast copper sustained release rate is solved, and high activity, high selectivity and good performance are achieved Reaction stability CuZnAl spinel solid solution catalyst.

CN119425703APending Publication Date: 2025-02-14SHANXI NORMAL UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411646877.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The copper-aluminum spinel catalyst has a slow release rate of copper too fast during the reaction, resulting in the unstable structure of the remaining defective spinel, transforming the crystallization occurs, and the catalytic activity decreases.

Method used

A second component Zn is introduced into the copper-aluminum spinel structure, and the sustained release rate of copper and the migration of Al are adjusted by external ions to modify the catalyst to improve its stability. The specific method includes weighing the precursor salts of Cu, Zn, and Al at 1:3 at the molar ratio of (Cu+Zn) and Al, mixing and ball milling, and then roasting in an air atmosphere to prepare a CuZnAl spinel solid solution catalyst. .

Benefits of technology

By introducing Zn component, the stability and activity of the catalyst are significantly improved, the sintering of Cu is delayed, and the selectivity of methanol reforming hydrogen production reaction and the stability of long-term operation are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425703A_ABST
    Figure CN119425703A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy and petrochemical engineering catalysts, and particularly discloses a preparation method and application of a copper-zinc-aluminum spinel solid solution catalyst. The Cu-Zn-Al spinel solid solution catalyst is prepared by ball-milling copper, zinc and aluminum precursors and then roasting at 800-1200 DEG C in the air atmosphere, and the preparation method is simple, does not need a large amount of solvent, is less in wastewater and avoids the influence of other impurity ions. The Cu-Zn-Al spinel solid solution catalyst prepared by the invention is used for methanol reforming hydrogen production reaction, the methanol conversion rate is as high as 95.5%, the H2 selectivity in the product is 74.8%, and the CO selectivity is 0.76%, so that the Cu-Zn-Al spinel solid solution catalyst has high activity, high selectivity and good reaction stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy and petrochemical catalysts, and specifically relates to a CuZnAl spinel solid solution catalyst and a preparation method and application thereof. Background Art

[0002] As a clean and efficient new energy source, hydrogen has great application prospects, such as hydrogenation reaction in chemical plants and hydrogen filling in fuel cells. There are many methods for industrial hydrogen production, among which methanol conversion has great advantages in small and medium-sized hydrogen-using enterprises and fuel cell fields. Methanol, as a hydrogen storage carrier, has become an ideal raw material for hydrogen production due to its high energy density, low carbon content, and advantages in transportation and storage.

[0003] The core of methanol reforming to produce hydrogen is the catalyst, among which copper-based catalysts have the advantages of low cost, high activity and good selectivity, and have become the focus of research and application. The catalysts that have been studied more are Cu-SiO2 and Cu-Al2O3 catalysts, and additives such as B, Ni, Fe, La, Ce, and Zn are added to improve the dispersibility of the active copper component and the interaction with the carrier, so that the activity and selectivity of the catalyst are greatly improved.

[0004] In recent years, copper-based catalysts with spinel structures have been 2+ The active copper is distributed in the voids of tetrahedrons and octahedrons, and is highly dispersed after reduction, so it has been widely studied. Nano-Cu particles formed after reduction pretreatment of spinel catalysts such as CuMn2O4, CuFe2O4, CuAl2O4, and CuCr2O4 show good catalytic performance in the reaction. On this basis, copper-aluminum spinel catalysts are used to directly participate in the catalytic reaction, and the active components are slowly released in situ during the reaction to gradually form new active centers, which effectively avoids the aggregation and growth of metal Cu in the active center during the pretreatment stage and significantly improves the catalytic performance. However, the gradual release of active copper in spinel is accompanied by the dynamic migration of Al, that is, the redistribution of Al in tetrahedrons and octahedrons. 3+ The violent rearrangement changes the remaining defective spinel structure, which may affect the aggregation and sintering behavior of reduced copper, thereby leading to changes in catalyst performance.

[0005] In view of the above problems, it is proposed to introduce a second group of components Zn into the copper-aluminum spinel structure to modify the catalyst, and use foreign ions to adjust the slow release rate of copper and the migration of Al to improve the stability of the catalyst. In the prior art, the Cu-Zn-Al spinel catalyst is prepared by wet ball milling. Compared with the commercial Cu / Zn / Al catalyst, it does not require pre-reduction treatment and has better reaction stability. However, water needs to be added during the wet ball milling process, and the resulting mixture has a high water content and needs to be dried. The steps are cumbersome, and the wastewater generated needs to be reprocessed, which increases the cost and energy consumption. In addition, the prepared catalyst has a small specific surface area, and the slow-released Cu is easily sintered after the catalyst runs for a long time, which reduces the catalytic efficiency. Summary of the invention

[0006] The purpose of the present invention is to solve the problems in the prior art that during the reaction of copper-aluminum spinel, the copper release rate is too fast, the defective spinel structure is unstable, and crystal transformation occurs, resulting in a decrease in catalytic activity. A copper-zinc-aluminum spinel solid solution catalyst with high activity, high selectivity and good reaction stability is provided, and the catalyst is applied to methanol reforming hydrogen production reaction.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing a CuZnAl spinel solid solution catalyst, comprising the following steps:

[0009] Step 1, weighing Cu, Zn, and Al precursor salts at a molar ratio of (Cu+Zn) to Al of 1:3 and mixing them thoroughly to obtain a precursor mixture;

[0010] Step 2, grinding or ball-milling the precursor mixture to obtain a ground or ball-milled precursor mixture;

[0011] Step 3: calcining the ground or ball-milled precursor mixture in an air atmosphere to obtain a CuZnAl spinel solid solution catalyst.

[0012] Preferably, the precursor salt in step 1 is nitrate, acetate, hydroxide or oxide of copper, aluminum or zinc.

[0013] Preferably, the time required for ball milling in step 2 is 1-24 hours.

[0014] Preferably, the calcination temperature in step 3 is in the range of 800-1200°C.

[0015] The present invention also provides a CuZnAl spinel solid solution catalyst, which is expressed as Cu 1-x Zn x Al3O 5.5, where x represents the number of atoms of the element Zn in the molecular formula, and its value ranges from 0 to 1.

[0016] The present invention also provides an application of a CuZnAl spinel solid solution catalyst in a methanol reforming hydrogen production reaction.

[0017] Preferably, the reaction conditions of the application are: the catalyst does not need to be pre-reduced with H2 before use, the reaction temperature is 210°C to 320°C, and the mass space velocity is 0.1h -1 ~2.2h -1 , the reaction pressure is from normal pressure to 2.0 MPa, H2O / CH3OH=1.0~3.0 (molar ratio).

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The catalyst preparation method is simple, does not require a large amount of solvent, produces little waste water, and avoids the influence of other impurity ions.

[0020] 2. According to the Cu, Zn, Al precursors and their ratios used in the present invention, the particle size of the generated spinel solid solution catalyst is between 7.0 and 10.0 nm, and the specific surface area is greater than 70 m 2 ·g -1 , which has a smaller particle size and a larger specific surface area than the spinel in the prior art, is conducive to the dispersion of slow-release Cu and delays the sintering of Cu, and has high activity, high selectivity and good reaction stability for methanol reforming reaction.

[0021] 3. The catalyst does not need to be pre-reduced with H2 before use. After the temperature is raised to the reaction temperature under nitrogen atmosphere, the methanol-water solution raw material can be directly added for reaction, which greatly simplifies the project start-up process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Cu obtained under different calcination temperature conditions 0.95 Zn 0.05 Al3O 5.5 Instantaneous conversion of catalyst.

[0023] Figure 2 Cu obtained under different calcination temperature conditions 0.95 Zn 0.05 Al3O 5.5 Catalyst CO selectivity.

[0024] Figure 3 Cu obtained under different calcination temperature conditions 0.50 Zn 0.50 Al3O 5.5 Instantaneous conversion of catalyst.

[0025] Figure 4Cu obtained under different calcination temperature conditions 0.80 Zn 0.20 Al3O 5.5 Instantaneous conversion of catalyst.

[0026] Figure 5 Cu 0.90 Zn 0.10 Al3O 5.5 The results of 1000 hours methanol reforming reaction at 250℃, 1.0MPa pressure and 2.184 weight hourly space velocity.

[0027] Figure 6 Cu 0.90 Zn 0.10 Al3O 5.5 The results of the methanol reforming reaction over the catalyst at 300°C, 1.0 MPa pressure and 2.184 WHSV for 1000 h.

[0028] Figure 7 Cu is obtained after calcination at 900℃ 1-x Zn x Al3O 5.5 XRD patterns of the catalysts.

[0029] Figure 8 Cu is obtained after calcination at 900℃ 0.90 Zn 0.10 Al3O 5.5 SEM image of the catalyst.

[0030] Fig. 9 Cu is obtained after calcination at 900℃ 0.90 Zn 0.10 Al3O 5.5 TPR diagram of the catalyst.

[0031] Fig.10 Cu is obtained after calcination at 900℃ 0.90 Zn 0.10 Al3O 5.5 Adsorption-desorption curve of the catalyst.

[0032] Fig.11 Cu is obtained after calcination at 900℃ 0.90 Zn 0.10 Al3O 5.5 Pore ​​size distribution of the catalyst. DETAILED DESCRIPTION

[0033] Example 1

[0034] 1. CuZnAl spinel solid solution catalyst Cu 0.95 Zn 0.05 Al3O 5.5 Preparation:

[0035] Step 1, according to the molar ratio of (Cu+Zn) to Al being 1:3, 9.26 g of copper hydroxide, 0.92 g of zinc acetate, and 63.90 g of aluminum nitrate were weighed respectively, placed in a grinder and mixed thoroughly to obtain a precursor mixture;

[0036] Step 2, placing the precursor mixture in a ball mill (QM2*2, Nantong Youbang Machinery Co., Ltd.), and ball milling for 3 hours to obtain a ball-milled precursor mixture;

[0037] Step 3: The ball-milled precursor mixture was calcined at 800°C, 900°C, 950°C, 1000°C, 1100°C, and 1200°C in an air atmosphere for 5 h to obtain a CuZnAl spinel solid solution catalyst Cu 0.95 Zn 0.05 Al3O 5.5 .

[0038] 2. Application and evaluation of catalysts:

[0039] The evaluation method of the catalyst of the present invention is as follows: the catalyst performance test is carried out on a 10mL continuous flow fixed bed, 10-14 mesh of the catalyst after crushing is taken and loaded into the reactor, and the temperature is directly raised to the reaction temperature at a heating rate of 3°C / min under a nitrogen atmosphere, and then the ventilation is stopped, and a methanol aqueous solution is transported by a double plunger micropump, and the raw materials enter the reactor for reaction after being preheated. After 20-24 hours from the start of the reaction, gas phase and liquid phase products are analyzed, and three gas chromatographs equipped with a Porapak T column, a TDX-01 column and a thermal conductivity cell detector, a methane converter and a hydrogen flame detector are used for analysis to obtain the conversion rate and selectivity.

[0040] Specifically:

[0041] Step 1: Add the catalyst Cu 0.95 Zn 0.05 Al3O 5.5 The catalyst was tableted and formed into a catalyst having a composition (mass fraction): CuO = 32.6%, ZnO = 1.7%, Al2O3 = 65.6%; the tableted catalyst was crushed and 3.0 g of catalyst particles of 10-14 mesh were selected and loaded into the reactor;

[0042] Step 2: In a nitrogen atmosphere, the temperature was raised to 250°C at a rate of 3°C / min, then the nitrogen was stopped and the feed was started (the molar ratio of H2O to CH3OH was 2.5) at a feed mass space velocity of 2.1h -1 , react under normal pressure.

[0043] 3. After 20 hours of reaction, the methanol conversion rate of the catalysts calcined at different temperatures was measured to be between 65.0% and 88.5%. As the reaction proceeded, the active Cu was gradually released, and the highest conversion rate was between 83.0% and 96.5% ( Figure 1 ), the H2 selectivity in the product is between 70.0% and 74.8%, and the CO selectivity is between 0.45% and 0.62% ( Figure 2 )

[0044] Example 2

[0045] 1. CuZnAl spinel solid solution catalyst Cu 0.50 Zn 0.50 Al3O 5.5 Preparation:

[0046] Step 1, according to the molar ratio of (Cu+Zn) to Al being 1:3, 4.88 g of copper hydroxide, 9.17 g of zinc acetate, and 63.90 g of aluminum nitrate were weighed respectively, placed in a grinder and fully mixed to obtain a precursor mixture;

[0047] Step 2, placing the precursor mixture in a ball mill (QM2*2, Nantong Youbang Machinery Co., Ltd.), and ball milling for 12 hours to obtain a ball-milled precursor mixture;

[0048] Step 3: The ball-milled precursor mixture was calcined at 800°C, 900°C, 950°C, 1000°C, 1100°C, and 1200°C in air atmosphere for 5 h to obtain a CuZnAl spinel solid solution catalyst Cu 0.50 Zn 0.50 Al3O 5.5 .

[0049] 2. Application and evaluation of catalysts:

[0050] The evaluation method of Example 2 is the same as that of Example 1, specifically:

[0051] Step 1: Add the catalyst Cu 0.5 Zn 0.5 Al3O 5.5 The catalyst was tableted and formed into a catalyst having a composition (mass fraction): CuO = 17.1%, ZnO = 17.4%, Al2O3 = 65.6%; the tableted catalyst was crushed and 3.0 g of catalyst particles of 10-14 mesh were selected and loaded into the reactor;

[0052] Step 2: In a nitrogen atmosphere, the temperature was raised to 250°C at a rate of 3°C / min, then the nitrogen was stopped and the feed was started (the molar ratio of H2O to CH3OH was 2.5) at a feed mass space velocity of 2.1h -1 , react under normal pressure.

[0053] 3. After 20 hours of reaction, the methanol conversion rate of the catalysts calcined at different temperatures was between 50.0% and 61.2% ( Figure 3 ), as the reaction proceeds, the active Cu is gradually released, the highest conversion rate is between 80.0% and 88.2%, the H2 selectivity in the product is between 72.1% and 74.9%, and the CO selectivity is less than 2.2%.

[0054] Example 3

[0055] 1. Cu-Zn-Al spinel solid solution catalyst Cu 0.80 Zn 0.20 Al3O 5.5 Preparation:

[0056] Step 1, according to the molar ratio of (Cu+Zn) to Al being 1:3, 7.82 g of copper hydroxide, 3.67 g of zinc acetate, and 23.40 g of aluminum hydroxide were weighed respectively, placed in a grinder and fully mixed to obtain a precursor mixture;

[0057] Step 2, placing the precursor mixture in a ball mill (QM2*2, Nantong Youbang Machinery Co., Ltd.), and ball milling for 12 hours to obtain a ball-milled precursor mixture;

[0058] Step 3: The ball-milled precursor mixture was calcined at 800°C, 900°C, 950°C, 1000°C, 1100°C, and 1200°C in air atmosphere for 5 h to obtain a CuZnAl spinel solid solution catalyst Cu 0.80 Zn 0.20 Al3O 5.5 .

[0059] 2. Application and evaluation of catalysts:

[0060] The evaluation method of the catalyst in Example 3 is the same as that in Example 1, specifically:

[0061] Step 1: Add the catalyst Cu 0.8 Zn 0.2 Al3O 5.5 The catalyst was tableted and formed into a catalyst having a composition (mass fraction): CuO = 27.44%, ZnO = 6.98%, Al2O3 = 65.58%; the tableted catalyst was crushed and 3.0 g of catalyst particles of 10-14 mesh were selected and loaded into the reactor;

[0062] Step 2: In a nitrogen atmosphere, the temperature was raised to 250°C at a rate of 3°C / min, then the nitrogen was stopped and the feed was started (the molar ratio of H2O to CH3OH was 2.5) at a feed mass space velocity of 2.1h -1 , react under normal pressure.

[0063] 3. After 20 hours of reaction, the methanol conversion rate of the catalysts calcined at different temperatures was between 60.2% and 80.0% ( Figure 4 ), as the reaction proceeds, the active Cu is gradually released, the highest conversion rate is in the range of 72.0-95.0%, the H2 selectivity in the product is 70.5-74.8%, and the CO selectivity is less than 5.3%.

[0064] Example 4

[0065] CuZnAl spinel solid solution catalyst Cu 0.90 Zn 0.10 Al3O 5.5 Preparation:

[0066] Step 1, according to the molar ratio of (Cu+Zn) to Al being 1:3, 8.76 g of copper hydroxide, 1.83 g of zinc acetate, and 63.90 g of aluminum nitrate were weighed respectively, placed in a grinder and mixed thoroughly to obtain a precursor mixture;

[0067] Step 2, placing the precursor mixture in a ball mill (QM2*2, Nantong Youbang Machinery Co., Ltd.), and ball milling for 3 hours to obtain a ball-milled precursor mixture;

[0068] Step 3: The ball-milled precursor mixture was calcined at 800°C, 900°C, 950°C, 1000°C, 1100°C, and 1200°C in an air atmosphere for 5 h to obtain a CuZnAl spinel solid solution catalyst Cu 0.9 Zn 0.1 Al3O 5.5 .

[0069] Catalyst Cu 0.90 Zn 0.10 Al3O 5.5 The results of the methanol reforming reaction at 250℃ / 300℃, 1.0MPa pressure and 2.184 WHSV for 1000 hours are as follows: Figure 5 and 6 As shown, it can be seen that the catalyst has a copper slow-release process during the reaction. At 250°C, the activity is highest after 72 hours of reaction, and the conversion rate reaches 94.8% and is basically stable. After the reaction temperature is increased to 300°C, the slow-release time is greatly shortened, and the highest activity can be reached after 49 hours of reaction, and the methanol conversion rate is 95.3%. As the reaction time increases, the activity gradually decreases. When the reaction time is 1000 hours, the methanol conversion rate drops to 49.9%.

[0070] The catalyst Cu obtained after calcination at 900°C in Example 1-4 0.95 Zn 0.05 Al3O5.5 , Cu 0.5 Zn 0.5 Al3O 5.5 , Cu 0.8 Zn 0.2 Al3O 5.5 and Cu 0.9 Zn 0.1 Al3O 5.5 The XRD results are as follows Figure 7 As shown in the figure, it can be seen that after doping with the auxiliary agent Zn, CuZnAl mixed spinel can be formed. When the Zn content is low, it enters the spinel skeleton structure together with Cu; when the doped Zn content is high, such as when the Zn / Cu molar ratio is greater than 0.20 / 0.80, at a calcination temperature of 900°C, there will be some free ZnO on the catalyst surface, which may react with the slowly released Cu and reduce the migration sintering performance of Cu.

[0071] The catalyst Cu obtained after calcination at 900°C in Example 4 0.90 Zn 0.10 Al3O 5.5 The SEM results are as follows Figure 8 As shown, it can be seen that the catalyst particles are small and dispersed more evenly, with a particle size between 7.0 and 10.0 nm.

[0072] The catalyst Cu obtained after calcination at 900°C in Example 4 0.90 Zn 0.10 Al3O 5.5 The TPR results are as follows Fig. 9 As shown, it can be seen that the catalyst contains a small amount of non-spinel copper species and most of the spinel copper. Non-spinel copper is dispersed on the surface of spinel, and a part of it reacts with the surrounding surplus Al-O species to form Cu-O-Al species, which can be reduced at a low temperature of 180-230°C. There is also a small amount of non-spinel copper existing as free CuO, which is reduced in the temperature range of 230-280°C. The reduction peak after the temperature is higher than 280°C belongs to the reduction of mixed spinel. Among them, the reduction peak in the range of 280-480°C belongs to the reduction of easily reduced mixed spinel species, and the reduction peak in the range of 480-880°C belongs to the reduction of difficult-to-reduce mixed spinel species.

[0073] The catalyst Cu obtained after calcination at 900°C in Example 4 0.90 Zn 0.10 Al3O 5.5 The adsorption-desorption curve of Fig.10 As shown in the figure, it can be seen that the catalyst presents a typical type IV adsorption isotherm, and its specific surface area is greater than 70m 2 ·g -1 .

[0074] The catalyst Cu obtained after calcination at 900°C in Example 4 0.90 Zn 0.10 Al3O 5.5 The pore size distribution of Fig.11 As shown, it can be seen that the pore size distribution of the catalyst is relatively concentrated in small and medium pores, mainly in the form of microporous structures within 0.5nm to 2nm and mesoporous structures within the range of 2 to 10nm, and the most probable pore size is 2.9nm.

Claims

1. A method for preparing a CuZnAl spinel solid solution catalyst, characterized in that: The steps include: Step 1, weighing a precursor compound according to a molar ratio of (Cu+Zn) to Al of 1:3 and mixing them thoroughly to obtain a precursor mixture; Step 2, grinding or ball-milling the precursor mixture to obtain a ground or ball-milled precursor mixture; Step 3: calcining the ground or ball-milled precursor mixture in an air atmosphere to obtain a CuZnAl spinel solid solution catalyst.

2. The method for preparing a CuZnAl spinel solid solution catalyst according to claim 1, characterized in that: The precursor compound in step 1 is nitrate, acetate, hydroxide or oxide of copper, aluminum or zinc.

3. The method for preparing a CuZnAl spinel solid solution catalyst according to claim 1, characterized in that: The time required for grinding or ball milling in step 2 is 1-24 hours.

4. The method for preparing a CuZnAl spinel solid solution catalyst according to claim 1, characterized in that: The calcination temperature in step 3 is 800-1200° C. and the calcination time is 5 hours.

5. The CuZnAl spinel solid solution catalyst prepared by the method according to any one of claims 1 to 4, characterized in that: The particle size of the catalyst is between 7.0 and 10.0 nm, and the specific surface area is greater than 70 m 2 ·g -1 The pore size distribution mainly consists of micropores in the range of 0.5nm to 2nm and mesopores in the range of 2 to 10nm. The expression is Cu 1-x Zn x Al3O 5.5 , where x represents the number of Zn atoms and its value ranges from 0 to 1.

6. An application of the CuZnAl spinel solid solution catalyst according to claim 5, characterized in that: Application in methanol reforming to produce hydrogen.

7. The use of a CuZnAl spinel solid solution catalyst according to claim 6, characterized in that: The reaction conditions of the application are: the catalyst does not need to be pre-reduced with H2 before use, the reaction temperature is 210°C to 310°C, the mass space velocity is 0.1h -1 ~2.2h -1 , the reaction pressure is from normal pressure to 2.0 MPa, and the molar ratio of H2O to CH3OH is 1.0-3.0:1.

Citation Information

Cited By

  • Petroleum product chemical composition automatic analysis system and method based on deep learning

    CN120847319A

  • Automatic analysis system and method for chemical composition of petroleum products based on deep learning

    CN120847319B

  • High-zinc-load mesoporous alumina-based CO2 hydrogenation catalyst as well as solvent-free preparation method and application thereof

    CN121797329A